Evaluation of Structure and Accessibility of Public Space Network in Kano Central Area with the Bid to Promote Urban Cohesion and Sustainability - Muktar, Muhammad; S. Ahmed, Abdulaziz (International Journal of Engineering and Technology, 2018)
There have been major concerns in the planning of both public and private spaces in Kano central area. Consequently, the entire urban fabric have been restructured due to uncontrolled developmental growth, population density, high cost of land value, unavailability of business location and poor accessibility to road network. These situations have brought about a physical and social shift in the position of Kano Central Business District (CBD) area, of which not prevented will continue to cause major urban cohesion and sustainability issue. Thus, this paper took a preemptive step to evaluate the existing problems and identify the major sustainability issues and where urban cohesion failed. A qualitative method was employed that does not only consider the study of morphological factors of the public space network in Kano CBD, but also the social, environmental and economic dynamics they generate. Thus, the data were collected through fieldwork (favoring direct contact with the territory), and analyzed using four key dimensions namely â€˜Form and legibilityâ€™, â€˜Access and Connectionsâ€™, â€˜Uses and Activitiesâ€™, then â€˜Sociability and Identificationâ€™. The findings revealed that the neighborhoods that make up the CBD have lot of abandoned buildings, insufficient access routes, poor drainage system, high volume of traffic that cause lot of pollution and proliferation of solid waste that makes road network impermeable, and an aesthetic eyesore. In view of these, the study recommends a set of urban intervention strategy capable of guiding the planning and redesign of public spaces in Kano CBD in order to promote urban cohesion and a sustainable environment.Â